PENGARUH KOMPETENSI DAN KEDISIPLINAN TERHADAP KINERJA MELALUI KEPUASAN KERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI RIAU - Pahmi, Syamsul; Indarti, Sri; Chairilsyah, Daviq (Jurnal Tepak Manajemen Bisnis, 2018)
This research was conducted at the Regional Development PlanningBoard of Riau Province. With the aim to know and analyze the influence ofcompetence and work discipline on the performance of employees who mediatejob satisfaction of employees at the Regional Development Planning Board ofRiau Province. Where the population is all employees of the RegionalDevelopment Planning Board of Riau Province which amounted to 115 people.The sample used in this research is 115 people taken with census method and dataprocessing using path analysis method with SPSS program.Based on the results ofthe test if the data by using the path analysis can be taken several conclusions,namely: Competence has a significant effect on employee performance at theRegional Development Planning Board of Riau Province, Work discipline has asignificant influence on employee performance at the Regional DevelopmentPlanning Board Riau Province, Satisfaction work has a significant influence onthe performance of employees at the Regional Development Planning Board ofRiau Province, Job Satisfaction can strengthen the influence of competence onemployee performance at the Regional Development Planning Board of RiauProvince, Job satisfaction can strengthen the influence of work discipline onemployee performance at the Regional Development Planning Agency of Riau.